The Martian [videorecording (DVD)] - Damon, Matt; Chastain, Jessica, 1977-; Wiig, Kristen, 1973-; Daniels, Jeff, 1955-; Weir, Andy (Twentieth Century Fox Home Entertainment, 2015)
After a bad storm blows across Mars Astronaut Mark Watney is presumed dead and left behind. Now stuck on a hostile planet he must find a way to signal to Earth and in the meantime, survive on limited supplies.